Marriage at the Crossroads : Law, Policy, and the Brave New World of Twenty-First-Century Families - Garrison, Marsha; Scott, Elizabeth S. (Cambridge : Cambridge University Press, 2012)
The institution of marriage is at a crossroads. Across most of the industrialized world, unmarried cohabitation and nonmarital births have skyrocketed while marriage rates are at record lows. These trends mask a new, idealized vision of marriage as a marker of success as well as a growing class divide in childbearing behavior: the children of better educated, wealthier individuals continue to be born into relatively stable marital unions while the children of less educated, poorer individuals are increasingly born and raised in more fragile, nonmarital households. The interdisciplinary approach offered by this edited volume provides tools to inform the debate and to assist policy makers in resolving questions about marriage at a critical juncture. Drawing on the expertise of social scientists and legal scholars, the book will be a key text for anyone who seeks to understand marriage as a social institution and to evaluate proposals for marriage reform.
Title from publisher's bibliographic system (viewed on 09 Oct 2015).